Analisis Tingkat Risiko Bahaya Area Kerja Laundrybox dengan Metode HIRARC - Pizaro , Lauw Vito; Efendy, Nur Meiliyanti; Andivas, Marulan (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
Laundry is a business sector that has the potential to cause the danger of work accidents. each potential danger has a different way of handling it. This research was conducted to find out the potential danger that could occur in a laundry business. HIRARC is a method used as a means of analyzing potential risks that may occur in work activities. From this research, it was found there are three activities or processes were identified as having potential dangers. These three activities consisted of spraying fragrances, using a clothes dryer, and inaccurate gas installation. Spraying fragrances has a high potential of danger with a risk rating value of 3 this potential danger can be prevented by using a facemask and glasses while working. The second activity is the use of a clothes dryer which has a low potential of danger with a risk rating value of 1, this activity can be prevented by implementing a safe action. The final work activity is a less careful gas installation with a moderate level of danger with a risk rating value of 2, more attention is needed when installing the regulator and using a good quality regulator. Keywords: HIRARC, laundry, risk